An anode flow field plate with catalytic activity, a preparation method and application thereof
Patent Information
- Application Number
- CN202310619805.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-29
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-05-29
AI Technical Summary
然而,高温烧结容易造成泡沫基体表面活性组分颗粒团聚,降低整体催化剂的活性
[0033]本发明提供一种具有催化活性的阳极流场板,采用微波水热工艺在泡沫镍基体上原位合成一种新型活性催化剂,构建一种泡沫镍负载活性催化剂的新型阳极流场板,通过对泡沫镍的厚度和面密度进行结构调控以及经预氧化处理后得到表面具有氧化镍的泡沫镍基底,使得泡沫镍基底既作为合成催化剂的基体又可将表面氧化镍作为的镍源参与反应;将六水硝酸镧、六水硝酸镍和钛酸四丁酯混合,再加入络合剂柠檬酸乙二胺四乙酸与金属镍离子形成稳定的络合物,提高反应稳定性,制备得到活性较高的La1.6Ti1.88Ni0.12O7的催化剂作为活性组分前驱体液;再利用活性组分前驱体液浸泡表面具有氧化镍的泡沫镍基底,经过微波水热合成处理后,制备得到具有催化活性的阳极流场板,从而能够有效的避免泡沫基体表面活性组分颗粒团聚,使得活性组分分散均匀和相间锚固力强,提高整体催化剂的活性。
Smart Images

Figure CN116722155B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of fuel cells, specifically relating to a catalytically active anode flow field plate, its preparation method, and its application. Background Technology
[0002] Solid oxide fuel cells (SOFCs) are power generation devices that directly convert the chemical energy of hydrocarbon fuels into electrical energy. They have unique advantages such as high efficiency, low (zero, when using H2 as fuel) emissions, no noise, and a wide range of fuel sources. SOFCs are not limited by the Carnot cycle, and even when using biomass gas fuel with a lower calorific value, the power generation efficiency can still reach 55%, and the combined heat and power efficiency can be as high as 80%.
[0003] Biomass gas, composed of H2, CO, and alkanes such as methane / ethane, is an ideal fuel for SOFCs. H2 and CO can be directly converted into electrical energy by electrochemical oxidation with O2 at the SOFC anode; methane / ethane needs to be reformed into H2 and CO, which then participate in electrochemical reactions at the anode functional layer.
[0004] There are two different strategies for reforming hydrocarbon fuels such as CH4 in SOFCs: external reforming and internal reforming. External reforming requires additional equipment and a separate supply of fuel gas, which increases the complexity of the SOFC system and reduces fuel utilization and power generation efficiency. Internal reforming involves directly introducing hydrocarbon fuel gas into the SOFC, utilizing the heat released from the electrode reaction to achieve fuel reforming inside the battery anode. Internal reforming requires the SOFC anode material to possess the dual functions of CH4 catalytic reforming activity and CO-H2 electrochemical oxidation reaction, severely limiting the selection of SOFC anode materials. To circumvent this drawback, researchers have added a separate reforming catalyst layer to the outside of the SOFC anode. This strategy is mostly used in coin cells; however, when applied to large-area batteries, the reforming catalyst layer and the anode functional layer can cause the battery to crack due to excessive thermal stress.
[0005] SOFC (Solar-Mechanical Fuel Cell) stacks consist of alternating stacks of individual cells and connectors connected in series vertically (height). The connectors link adjacent cells together and simultaneously distribute fuel gas and air to both cells. Gas distribution plates are located above and below the connectors, uniformly distributing fuel gas and air to the anode and cathode of the cell, respectively. Nickel foam, with its three-dimensional porous network structure, maintains a metallic state under a reducing atmosphere and exhibits certain mechanical compatibility. Therefore, nickel foam is often used as a fuel gas distribution plate on the anode side of the connector, contacting the anode to collect current. Loading biomass gas catalysts onto nickel foam to construct a novel catalytically active anode flow field plate allows the nickel foam to effectively act as a current collector while also playing a role in catalytic reforming. This not only greatly simplifies the battery fabrication process but also overcomes the technical challenges of the mutual constraints between chemical reforming and electrochemical oxidation reactions on the same anode, as well as carbon deposition on Ni-based anodes.
[0006] The nickel foam matrix determines the macroscopic morphology, overall structure, mechanical strength, and mass and heat transfer capabilities of the anode gas flow field plate in an SOFC stack. The active catalyst component is the decisive factor influencing the catalyst performance of the anode flow field plate. Supporting a multi-component catalyst with excellent activity, good stability, and long lifetime on nickel foam and forming a strong interphase bond is key to preparing efficient and stable catalysts. Traditional processes such as coating, solution impregnation, ion exchange, and sol-gel can load the active catalyst component onto the foam matrix. However, these processes rely solely on binders to physically bond the active catalyst component to the matrix, making catalyst detachment prone to occur, especially under the high space velocities of SOFC stacks, where stack performance degradation can be amplified exponentially. To mitigate this problem, the foam matrix and the supported active catalyst component are calcined at high temperatures to create chemical bonds between the two phases. However, high-temperature sintering easily causes agglomeration of active component particles on the foam matrix surface, reducing the overall catalyst activity. The strategy of in-situ synthesis of high-performance biomass gas catalysts in foamed Ni matrix can solve the problems of uneven dispersion of active components and poor interphase anchoring.
[0007] It is evident that existing preparation processes are prone to causing agglomeration of active component particles on the surface of the foam matrix, uneven dispersion of active components, and poor interphase anchoring, leading to a reduction in the overall catalyst activity. Summary of the Invention
[0008] To address the aforementioned technical problems, this invention provides a catalytically active anode flow field plate, its preparation method, and its application. This method avoids the agglomeration of active component particles on the surface of the foam matrix, resulting in uniform dispersion of the active components and strong interphase anchoring, thereby improving the overall catalyst activity.
[0009] This invention is achieved through the following technical solution:
[0010] A method for preparing a catalytically active anode flow field plate, comprising:
[0011] S1: Structural regulation of nickel foam and pre-oxidation treatment to obtain a nickel foam substrate with nickel oxide on the surface;
[0012] S2: Lanthanum nitrate hexahydrate, nickel nitrate hexahydrate and tetrabutyl titanate are dissolved in a solvent in a preset ratio to obtain a mixture. Citric acid and ethylenediaminetetraacetic acid are then added to the mixture to obtain the precursor solution of the active component.
[0013] S3: A catalytically active anode flow field plate is prepared by soaking a nickel foam substrate with nickel oxide on its surface in an active component precursor liquid and then performing microwave hydrothermal synthesis treatment.
[0014] Preferably, the specific process for structural control of nickel foam in S1 is as follows:
[0015] The nickel foam is cut into block structures, and then rolled twice on rollers to adjust the thickness and areal density of the nickel foam. The rolled nickel foam is then soaked in dilute hydrochloric acid solution for 5-15 minutes, rinsed with distilled water, and then ultrasonically cleaned in dilute hydrochloric acid solution, anhydrous ethanol, acetone and deionized water for 25-30 minutes respectively. Finally, it is vacuum dried at 50-70℃ for 5-8 hours to obtain a clean nickel foam substrate.
[0016] Preferably, the thickness of the nickel foam after the first roll forming is 1.2–1.3 mm, the thickness of the nickel foam after the second roll forming is 0.9–1.1 mm, and the areal density of the nickel foam after roll forming reaches 0.40–0.45 kg / m³. 2 The original nickel foam thickness was 1.5 mm; the concentration of the dilute hydrochloric acid solution was 1 mol / L to 2 mol / L.
[0017] Preferably, the specific process after pre-oxidizing the nickel foam in S1 is as follows:
[0018] The nickel foam substrate was heated in air at a temperature of 400℃~700℃ at a heating rate of 5~10℃ / min. -1 After reaching the set temperature, keep it at that temperature for 8-15 minutes to perform high-temperature pre-oxidation treatment. After cooling to room temperature, a nickel foam substrate with nickel oxide on the surface is obtained.
[0019] Preferably, the specific process of S2 is as follows:
[0020] Step 1: Dissolve lanthanum nitrate hexahydrate, nickel nitrate hexahydrate, and tetrabutyl titanate in 80-100 ml of anhydrous ethanol at a mass ratio of 30-40 g: 2-4 g: 25-34 g. Then mix the mixture with ethylenediaminetetraacetic acid and add 40-45 g of citric acid and stir to form solution I.
[0021] Step 2: Dissolve 20-32g of ethylenediaminetetraacetic acid in 80-100ml of deionized water and stir at 80℃ to form solution II;
[0022] Step 3: Add solution II to solution I, adjust the pH to 7.5-8.5 with ammonia, stir at 80℃ for 2 hours to obtain the precursor solution of the active component.
[0023] Preferably, the specific steps of S3 are as follows:
[0024] The nickel foam substrate with nickel oxide on its surface was immersed in the precursor liquid of the active component, heated in stages, and then subjected to microwave hydrothermal synthesis treatment to obtain the reacted nickel foam substrate. The surface gel of the reactants on the reacted nickel foam substrate was then removed, and the substrate was then washed several times with deionized water and anhydrous ethanol to obtain the catalyst-loaded anode flow field plate.
[0025] The specific process of segmented heating is as follows: the nickel foam substrate with nickel oxide on the surface is immersed in the precursor liquid of the active component and heated to 100°C for 3-5 minutes, then heated to 180°C for 2-4 minutes, then heated to 200°C for 1-2 minutes, and held at 200°C for 60 minutes. After cooling to room temperature, the reacted nickel foam substrate is obtained.
[0026] A catalytically active anode flow field plate is prepared by the above-described method.
[0027] The application of a catalytically active anode flow field plate in solid oxide fuel cell stacks includes:
[0028] A layer of nickel paste is brushed onto the anode side of the metal connector, and the catalytically active anode flow field plate is bonded to the metal connector under a pressure of 0.1 to 0.3 MPa. Then, it is assembled into a stack by alternately stacking and installing side covers with solid oxide fuel cell sheets. The anode flow field plate and the metal connector are tightly connected under the high-temperature operation environment of the stack.
[0029] Preferably, the cathode side of the metal connector uses a stainless steel corrugated plate as an air flow field plate, and the anode side of the metal connector uses an anode flow field plate with catalytic activity.
[0030] Preferably, the specific process of high-temperature in-situ calcination of the fuel cell stack is as follows:
[0031] A hydrogen-nitrogen mixture is introduced into the anode of the fuel cell stack, while air is introduced into the anode. The temperature is raised to 600°C in 200-300 minutes and held for 2-3 hours to ensure sintering between the nickel foam and the metal connector. The temperature is then raised to 850°C in 120 minutes and held for 2 hours to achieve in-situ calcination of the catalyst on the nickel foam. Subsequently, the temperature is lowered to 750°C, and the anode gas of the fuel cell stack is switched to hydrogen to achieve in-situ precipitation of nanoparticle catalyst. Finally, the fuel gas in the solid oxide fuel cell is converted to biomass gas, realizing the stable operation of the fuel cell stack fueled by biomass gas.
[0032] Compared with the prior art, the present invention has the following beneficial technical effects:
[0033] This invention provides a catalytically active anode flow field plate. A novel active catalyst is synthesized in situ on a nickel foam substrate using a microwave hydrothermal process, constructing a novel anode flow field plate with a nickel foam-supported active catalyst. By structurally controlling the thickness and areal density of the nickel foam and pre-oxidizing it, a nickel foam substrate with nickel oxide on its surface is obtained. This allows the nickel foam substrate to serve both as the substrate for catalyst synthesis and as a nickel source for the reaction using the surface nickel oxide. Lanthanum nitrate hexahydrate, nickel nitrate hexahydrate, and tetrabutyl titanate are mixed, and then a complexing agent, ethylenediaminetetraacetic acid citrate, is added to form a stable complex with metallic nickel ions, improving reaction stability and preparing a highly active La. 1.6 Ti 1.88 Ni 0.12 O7 catalyst is used as the precursor liquid for active components; a nickel foam substrate with nickel oxide on its surface is then soaked in the precursor liquid for active components, and after microwave hydrothermal synthesis treatment, an anode flow field plate with catalytic activity is prepared. This effectively avoids the agglomeration of active component particles on the surface of the foam substrate, resulting in uniform dispersion of active components and strong interphase anchoring force, thereby improving the overall activity of the catalyst.
[0034] This invention also provides the application of a catalytically active anode flow field plate in a solid oxide fuel cell stack. This catalytically active anode flow field plate acts as the SOFC anode current collector while also playing a role in the catalytic reforming of biomass gas, thereby achieving stable operation of the biomass gas-fueled stack. Using this catalytically active anode flow field plate in the SOFC stack can separate the anode electrochemical reaction from the internal reforming chemical reaction, and concentrate both within the stack, avoiding the low efficiency of external reforming systems. Simultaneously, it utilizes the endothermic nature of the reforming reaction and the exothermic nature of the oxidation reaction to balance the stack temperature. Attached Figure Description
[0035] Figure 1 A schematic diagram of a solid oxide fuel cell stack with internal reforming of biomass gas.
[0036] Figure 2This is a schematic diagram of the anode side of the metal connector;
[0037] Figure 3 A schematic diagram of the microstructure of a porous nickel foam network;
[0038] Figure 4 A schematic diagram of nickel foam using the supported catalyst of the present invention;
[0039] Figure 5 Here are schematic diagrams of the microstructure of the active component catalyst prepared in the sintered state according to the present invention; (a) sintered state diagram of the catalyst, (b) reduced state diagram of the catalyst;
[0040] Figure 6 The stability test curves of the fuel cell stack assembled using the novel anode flow field plate when fueled by biomass gas are shown.
[0041] In the diagram: 1-Top cover of the fuel cell stack, 2-Sealing material, 3-SOFC cell, 4-Metal connector, 5-Side cover, 6-Bottom cover, 7-Anode side sealing strip of metal connector, 8-Nickel foam. Detailed Implementation
[0042] The present invention will be further described in detail below with reference to specific embodiments. These descriptions are for explanation purposes only and are not intended to limit the scope of the invention.
[0043] To enable those skilled in the art to better understand the present invention, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.
[0044] Example 1
[0045] The novel catalytically active anode flow field plate preparation process of this invention includes pretreatment of nickel foam, La... 1.6 Ti 1.88 Ni 0.12 Preparation of O7 catalyst and loading of active components. The main preparation process includes the following steps:
[0046] 1. Structural control of nickel foam
[0047] First, cut 1.5mm thick commercial Ni foam into 110×110mm pieces. 2 The foamed nickel was then subjected to two rolling processes on rollers to adjust its thickness and areal density. The rollers were adjusted so that the foamed nickel thickness was 1.2 mm after the first rolling and 0.9 mm after the second rolling, achieving an areal density of 0.40 kg / m³.2 .
[0048] Subsequently, nickel foam cut to a suitable experimental area was soaked in 2 mol / L dilute hydrochloric acid for 10 minutes to increase the surface roughness, and then rinsed clean with distilled water. The nickel foam was then ultrasonically cleaned sequentially in dilute hydrochloric acid, anhydrous ethanol, acetone, and deionized water for 30 minutes each, and then vacuum dried at 60°C for 6 hours to obtain a clean nickel foam substrate. Figure 3 This is a schematic diagram of the microstructure of a porous nickel foam network.
[0049] 2. Pre-oxidation treatment of nickel foam
[0050] The washed and dried nickel foam was placed in a ceramic boat and heated in a muffle furnace at 400°C with a heating rate of 5°C / min under air atmosphere. -1 After reaching the set temperature, hold for 10 minutes, then cool with the furnace to room temperature to obtain a nickel foam substrate with nickel oxide on the surface.
[0051] 3. Preparation of precursor fluids for active components
[0052] Weigh out 30g of reagents (analytical grade) La(NO3)3·6H2O, 4g of Ni(NO3)2·6H2O, and 34g of [CH3(CH2)3O]4Ti, and dissolve them in 80g of anhydrous ethanol. Stir with a glass rod until completely dissolved. Weigh out 45g of citric acid and add it to the solution. Stir magnetically until completely dissolved to form solution 1. Dissolve 20g of EDTA in 80g of deionized water and stir at 80℃ to form solution 2. Add solution 2 to solution 1, adjust the pH to 8.0 with ammonia, and stir magnetically at 80℃ for 2 hours to obtain a clear solution, which is the precursor solution of the active component.
[0053] 4. Microwave hydrothermal synthesis of active component catalysts
[0054] Nickel foam serves as both the matrix for the synthesis catalyst and the nickel source in the reaction. A nickel foam substrate with a nickel oxide surface is placed in a polytetrafluoroethylene (PTFE) microwave reactor liner. A prepared clarified solution is then added to the vessel, completely immersing the nickel foam. The reactor is then placed in a microwave oven, and the temperature is increased to 100°C in 3 minutes, to 180°C in 2 minutes, and to 200°C in 1 minute, held at 200°C for 60 minutes. After a programmed cooling process to room temperature, the reactor is removed, the gel on the surface of the nickel foam is scraped off, and the nickel foam is washed three times each with deionized water and anhydrous ethanol to obtain the catalyst-supported anode flow field plate. Finally, the catalyst-supported nickel foam is flattened under a press for later use. Figure 4 This is a schematic diagram of nickel foam using the catalyst supported by this invention. Figure 5The diagram shows the microstructure of the active component catalyst in the sintered state prepared in this invention. (a) is a diagram of the catalyst in the sintered state, and (b) is a diagram of the catalyst after reduction. The sintered particles have smooth surfaces, while a large number of nanoparticles are precipitated on the surface of the particles after reduction.
[0055] 5. Assembly of metal connectors
[0056] The cathode side of the metal connector uses a stainless steel corrugated plate as the airflow field plate, while the anode side uses an anode flow field plate with a catalyst-loaded substrate obtained through the aforementioned process as the flow field plate for biomass gas fuel. A layer of nickel paste is brushed onto the anode side of the metal connector, and the foamed nickel is bonded to the metal connector under a pressure of 0.1 MPa to obtain a composite connector, such as... Figure 2 The diagram shown is a schematic of the anode side of the metal connector;
[0057] 6. In-situ calcination of catalysts
[0058] The composite connector and SOFC solid oxide fuel cell cells are alternately stacked and assembled, and side covers are installed to form a fuel cell stack. Under the high-temperature operation environment of the fuel cell stack, the interface between the anode flow field plate and the metal connector is tightly connected by sintering. A hydrogen-nitrogen mixture is introduced into the anode of the fuel cell stack, and air is introduced into the anode. The temperature is raised to 600℃ in 200 minutes and held for 2 hours to ensure that the nickel foam and the metal connector are sintered and connected, reducing the interfacial resistance between the cell and the connector. The temperature is raised to 850℃ in 120 minutes and held for 2 hours to achieve in-situ calcination of the catalyst on the nickel foam. Then, the temperature is lowered to 750℃ and the anode gas is switched to hydrogen to achieve in-situ precipitation of nanoparticle catalyst, forming a highly active and stable catalyst. Finally, the fuel gas is converted into biomass gas to achieve stable operation of the fuel cell stack. Figure 1 This is a schematic diagram of a solid oxide fuel cell stack with internal reforming of biomass gas. In the diagram, the stack top cover is 1, the sealing material is 2, the SOFC cell is 3, the metal connector is 4, the side cover is 5, the bottom cover is 6, the metal connector anode side sealing strip is 7, and the foamed nickel is 8.
[0059] like Figure 6To test the stability of a fuel cell stack assembled using a novel anode flow field plate when fueled by biomass gas, single-cell stacks assembled with catalytically active and conventional anode flow field plates were discharged at 40A in biomass gas fuel, and the voltage change over time was plotted. It can be seen that the battery using the catalytically active anode flow field plate operates at approximately 0.85V and operates stably for 100 hours without degradation. The excellent stability of the battery mainly stems from the highly efficient catalytic reforming activity of the anode flow field plate. In contrast, the battery using the conventional anode flow field plate operates at approximately 0.81V, and after 70 hours, the voltage drops sharply, primarily due to carbon buildup at the anode caused by hydrocarbon fuel cracking, leading to battery rupture. The catalytically active anode flow field plate of this invention, while acting as the anode current collector in SOFCs, also plays a role in the catalytic reforming of biomass gas, thereby achieving stable operation of biomass gas fuel cell stacks. Using this catalytically active anode flow field plate in SOFC stacks can separate the anode electrochemical reaction from the internal reforming chemical reaction and concentrate both inside the stack, avoiding the low efficiency of external reforming systems. At the same time, it utilizes the endothermic nature of the reforming reaction and the exothermic nature of the oxidation reaction to balance the stack temperature.
[0060] Example 2
[0061] 1. Structural control of nickel foam
[0062] First, cut 1.5mm thick commercial Ni foam into 110×110mm pieces. 2 The foamed nickel was then subjected to two rolling processes on rollers to adjust its thickness and areal density. The rollers were adjusted so that the foamed nickel thickness was 1.3 mm after the first rolling and 1.1 mm after the second rolling, achieving an areal density of 0.45 kg / m³. 2 .
[0063] Subsequently, nickel foam cut to a suitable experimental area was soaked in 1 mol / L dilute hydrochloric acid for 15 minutes to increase the surface roughness of the nickel foam, and then rinsed clean with distilled water. The nickel foam was then ultrasonically cleaned in dilute hydrochloric acid, anhydrous ethanol, acetone and deionized water in sequence for 25 minutes, and then vacuum dried at 50°C for 8 hours to obtain a clean nickel foam substrate.
[0064] 2. Pre-oxidation treatment of nickel foam
[0065] The washed and dried nickel foam was placed in a ceramic boat and heated in a muffle furnace at 700°C with a heating rate of 10°C / min under air atmosphere. -1 After reaching the set temperature, hold for 8 minutes, then cool with the furnace to room temperature to obtain a foamed nickel substrate with nickel oxide on the surface.
[0066] 3. Preparation of precursor fluids for active components
[0067] Weigh out 40g of reagents (analytical grade) La(NO3)3·6H2O, 2g of Ni(NO3)2·6H2O, and 25g of [CH3(CH2)3O]4Ti, and dissolve them in 100ml of anhydrous ethanol. Stir with a glass rod until completely dissolved. Weigh out 40g of citric acid and add it to the solution. Stir magnetically until completely dissolved to form solution 1. Dissolve 32g of EDTA in 100ml of deionized water and stir at 80℃ to form solution 2. Add solution 2 to solution 1, adjust the pH to 7.5 with ammonia, and stir magnetically at 80℃ for 2 hours to obtain a clear solution, which is the precursor solution of the active component.
[0068] 4. Microwave hydrothermal synthesis of active component catalysts
[0069] Nickel foam serves as both the matrix for the synthesis catalyst and the nickel source in the reaction. A nickel foam substrate with nickel oxide on its surface is placed in a polytetrafluoroethylene microwave reactor liner. A prepared clarified solution is then added to the reactor, completely submerging the nickel foam. The reactor is then placed in a microwave oven, where the temperature is raised to 100°C in 5 minutes, to 180°C in 4 minutes, and to 200°C in 2 minutes. This temperature is maintained at 200°C for 60 minutes. After the temperature is reduced to room temperature, the reactor is removed, and the gel on the surface of the nickel foam is scraped off. The nickel foam is then washed three times each with deionized water and anhydrous ethanol to obtain the catalyst-supported anode flow field plate. Finally, the catalyst-supported nickel foam is flattened under a press for later use.
[0070] 5. Assembly of metal connectors
[0071] The cathode side of the metal connector uses a stainless steel corrugated plate as the air flow field plate, while the anode side uses an anode flow field plate with a catalyst loaded after the above process as the flow field plate for biomass gas fuel. A layer of nickel paste is brushed onto the anode side of the metal connector, and the foamed nickel is bonded to the connector under a pressure of 0.3 MPa to obtain a composite connector.
[0072] 6. In-situ calcination of catalysts
[0073] The composite connector and SOFC solid oxide fuel cell cells are alternately stacked and assembled, and side covers are installed to form a fuel cell stack. Under the high-temperature operation environment of the fuel cell stack, the interface between the anode flow field plate and the metal connector is tightly connected by sintering. A hydrogen-nitrogen mixture is introduced into the anode of the fuel cell stack, and air is introduced into the anode. The temperature is raised to 600℃ in 200 minutes and held for 2 hours to ensure that the nickel foam and the metal connector are sintered and connected, reducing the interfacial resistance between the cell and the connector. The temperature is raised to 850℃ in 120 minutes and held for 2 hours to achieve in-situ calcination of the catalyst on the nickel foam. Then, the temperature is lowered to 750℃ and the anode gas is switched to hydrogen to achieve in-situ precipitation of nanoparticle catalyst, forming a highly active and stable catalyst. Finally, the fuel gas is converted into biomass gas to achieve stable operation of the fuel cell stack.
[0074] Example 3
[0075] 1. Structural control of nickel foam
[0076] First, cut 1.5mm thick commercial Ni foam into 110×110mm pieces. 2 The foamed nickel was then subjected to two rolling processes on rollers to adjust its thickness and areal density. The rollers were adjusted so that the foamed nickel thickness was 1.25 mm after the first rolling and 1.0 mm after the second rolling, achieving an areal density of 0.43 kg / m³. 2 .
[0077] Subsequently, nickel foam cut to a suitable experimental area was soaked in 1.5 mol / L dilute hydrochloric acid for 5 minutes to increase the surface roughness of the nickel foam, and then rinsed clean with distilled water. The nickel foam was then ultrasonically cleaned in dilute hydrochloric acid, anhydrous ethanol, acetone and deionized water for 25 minutes in sequence, and then vacuum dried at 70°C for 5 hours to obtain a clean nickel foam substrate.
[0078] 2. Pre-oxidation treatment of nickel foam
[0079] The washed and dried nickel foam was placed in a ceramic boat and heated in a muffle furnace at 500°C with a heating rate of 8°C / min under air atmosphere. -1 After reaching the set temperature, the temperature is held for 15 minutes and then cooled to room temperature in the furnace to obtain a foamed nickel substrate with nickel oxide on the surface.
[0080] 3. Preparation of precursor fluids for active components
[0081] Weigh out 35g of reagents (analytical grade) La(NO3)3·6H2O, 3g of Ni(NO3)2·6H2O, and 30g of [CH3(CH2)3O]4Ti, and dissolve them in 90ml of anhydrous ethanol. Stir with a glass rod until completely dissolved. Weigh out 42g of citric acid and add it to the solution. Stir magnetically until completely dissolved to form solution 1. Dissolve 24g of EDTA in 90ml of deionized water and stir at 80℃ to form solution 2. Add solution 2 to solution 1, adjust the pH to 7.5 with ammonia, and stir magnetically at 80℃ for 2 hours to obtain a clear solution, which is the precursor solution of the active component.
[0082] 4. Microwave hydrothermal synthesis of active component catalysts
[0083] Nickel foam serves as both the matrix for the synthetic catalyst and the nickel source in the reaction. A nickel foam substrate with nickel oxide on its surface is placed in a polytetrafluoroethylene microwave reactor liner. A prepared clarified solution is then added to the reactor, completely submerging the nickel foam. The reactor is then placed in a microwave oven, where the temperature is raised to 100°C in 4 minutes, to 180°C in 3 minutes, and to 200°C in 1.5 minutes. The temperature is maintained at 200°C for 60 minutes. After a programmed cooling process to room temperature, the reactor is removed, and the gel on the surface of the nickel foam is scraped off. The nickel foam is then washed five times each with deionized water and anhydrous ethanol to obtain the catalyst-supported anode flow field plate. Finally, the catalyst-supported nickel foam is flattened under a press for later use.
[0084] 5. Assembly of metal connectors
[0085] The cathode side of the metal connector uses a stainless steel corrugated plate as the air flow field plate, while the anode side uses an anode flow field plate with a catalyst loaded after the above process as the flow field plate for biomass gas fuel. A layer of nickel paste is brushed onto the anode side of the metal connector, and the foamed nickel is bonded to the connector under a pressure of 0.2 MPa to obtain a composite connector.
[0086] 6. In-situ calcination of catalysts
[0087] The composite connector and SOFC solid oxide fuel cell cells are alternately stacked and assembled, and side covers are installed to form a fuel cell stack. Under the high-temperature operation environment of the fuel cell stack, the interface between the anode flow field plate and the metal connector is tightly connected by sintering. A hydrogen-nitrogen mixture is introduced into the anode of the fuel cell stack, and air is introduced into the anode. The temperature is raised to 600℃ in 300 minutes and held for 3 hours to ensure that the nickel foam and the metal connector are sintered and connected, reducing the interfacial resistance between the cell and the connector. The temperature is raised to 850℃ in 120 minutes and held for 2 hours to achieve in-situ calcination of the catalyst on the nickel foam. Then, the temperature is lowered to 750℃ and the anode gas is switched to hydrogen to achieve in-situ precipitation of nanoparticle catalyst, forming a highly active and stable catalyst. Finally, the fuel gas is converted into biomass gas to achieve stable operation of the fuel cell stack.
[0088] Example 4
[0089] 1. Structural control of nickel foam
[0090] First, cut 1.5mm thick commercial Ni foam into 90×90mm pieces. 2 The foamed nickel was then subjected to two rolling processes on rollers to adjust its thickness and areal density. The rollers were adjusted so that the foamed nickel thickness was 1.25 mm after the first rolling and 1.0 mm after the second rolling, achieving an areal density of 0.42 kg / m³. 2 .
[0091] Subsequently, nickel foam cut to a suitable experimental area was soaked in 1.0 mol / L dilute hydrochloric acid for 10 minutes to increase the surface roughness of the nickel foam, and then rinsed clean with distilled water. The nickel foam was then ultrasonically cleaned in dilute hydrochloric acid, anhydrous ethanol, acetone and deionized water for 30 minutes in sequence, and then vacuum dried at 70°C for 5 hours to obtain a clean nickel foam substrate.
[0092] 2. Pre-oxidation treatment of nickel foam
[0093] The washed and dried nickel foam was placed in a ceramic boat and heated in a muffle furnace at 600°C with a heating rate of 8°C / min under air atmosphere. -1 After reaching the set temperature, the temperature is held for 15 minutes and then cooled to room temperature in the furnace to obtain a foamed nickel substrate with nickel oxide on the surface.
[0094] 3. Preparation of precursor fluids for active components
[0095] Weigh out 35g of reagents (analytical grade) La(NO3)3·6H2O, 3g of Ni(NO3)2·6H2O, and 30g of [CH3(CH2)3O]4Ti, and dissolve them in 90ml of anhydrous ethanol. Stir with a glass rod until completely dissolved. Weigh out 44g of citric acid and add it to the solution. Stir magnetically until completely dissolved to form solution 1. Dissolve 24g of EDTA in 90ml of deionized water and stir at 80℃ to form solution 2. Add solution 2 to solution 1, adjust the pH to 7.5 with ammonia, and stir magnetically at 80℃ for 2 hours to obtain a clear solution, which is the precursor solution of the active component.
[0096] 4. Microwave hydrothermal synthesis of active component catalysts
[0097] Nickel foam serves as both the matrix for the synthetic catalyst and the nickel source in the reaction. A nickel foam substrate with nickel oxide on its surface is placed in a polytetrafluoroethylene microwave reactor liner. A prepared clarified solution is then added to the reactor, completely submerging the nickel foam. The reactor is then placed in a microwave oven, where the temperature is raised to 100°C in 4 minutes, to 180°C in 3 minutes, and to 200°C in 1.5 minutes. The temperature is maintained at 200°C for 60 minutes. After a programmed cooling process to room temperature, the reactor is removed, and the gel on the surface of the nickel foam is scraped off. The nickel foam is then washed five times each with deionized water and anhydrous ethanol to obtain the catalyst-supported anode flow field plate. Finally, the catalyst-supported nickel foam is flattened under a press for later use.
[0098] 5. Assembly of metal connectors
[0099] The cathode side of the metal connector uses a stainless steel corrugated plate as the air flow field plate, while the anode side uses an anode flow field plate with a catalyst loaded after the above process as the flow field plate for biomass gas fuel. A layer of nickel paste is brushed onto the anode side of the metal connector, and the foamed nickel is bonded to the connector under a pressure of 0.2 MPa to obtain a composite connector.
[0100] 6. In-situ calcination of catalysts
[0101] The composite connector and SOFC solid oxide fuel cell cells are alternately stacked and assembled, and side covers are installed to form a fuel cell stack. Under the high-temperature operation environment of the fuel cell stack, the interface between the anode flow field plate and the metal connector is tightly connected by sintering. A hydrogen-nitrogen mixture is introduced into the anode of the fuel cell stack, and air is introduced into the anode. The temperature is raised to 600℃ in 300 minutes and held for 3 hours to ensure that the nickel foam and the metal connector are sintered and connected, reducing the interfacial resistance between the cell and the connector. The temperature is raised to 850℃ in 120 minutes and held for 2 hours to achieve in-situ calcination of the catalyst on the nickel foam. Then, the temperature is lowered to 750℃ and the anode gas is switched to hydrogen to achieve in-situ precipitation of nanoparticle catalyst, forming a highly active and stable catalyst. Finally, the fuel gas is converted into biomass gas to achieve stable operation of the fuel cell stack.
[0102] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used herein in the specification of this invention is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0103] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Those skilled in the art can readily implement the present invention based on the accompanying drawings and the above description. However, any modifications, alterations, or variations made by those skilled in the art without departing from the scope of the present invention, utilizing the disclosed technical content, are equivalent embodiments of the present invention. Furthermore, any modifications, alterations, or variations made to the above embodiments based on the essential technology of the present invention are still within the protection scope of the present invention.
Claims
1. A method for preparing a catalytically active anode flow field plate for use in a solid oxide fuel cell stack, characterized in that, include: S1: Structural regulation of nickel foam and pre-oxidation treatment to obtain a nickel foam substrate with nickel oxide on the surface; S2: Lanthanum nitrate hexahydrate, nickel nitrate hexahydrate and tetrabutyl titanate are dissolved in a solvent in a predetermined ratio to obtain a mixture. Citric acid and ethylenediaminetetraacetic acid are then added to the mixture to obtain the precursor liquid of the active component of the La1.6Ti1.88Ni0.12O7 catalyst. S3: A nickel foam substrate with nickel oxide on its surface is soaked in an active component precursor liquid and then subjected to microwave hydrothermal synthesis to obtain an anode flow field plate with a catalyst supported. A layer of nickel paste is brushed onto the anode side of the metal connector, and the anode flow field plate with the catalyst supported is bonded together with the metal connector under a pressure of 0.1~0.3 MPa. It is then stacked alternately with solid oxide fuel cell sheets and assembled into a stack by installing side covers. A tight connection between the anode flow field plate and the metal connector is achieved under the high-temperature operating environment of the stack. The specific process for the high-temperature operating environment of the fuel cell stack is as follows: A hydrogen-nitrogen mixture is introduced into the anode of the fuel cell stack, and air is introduced into the cathode. The temperature is raised to 600 °C in 200-300 min and held for 2-3 h to ensure sintering connection between the catalyst-loaded anode flow field plate and the metal connector. The temperature is then raised to 850 °C in 120 min and held for 2 h to achieve in-situ calcination of the catalyst on the anode flow field plate. Subsequently, the temperature is lowered to 750 °C, and the anode gas of the fuel cell stack is switched to hydrogen to achieve in-situ precipitation of nanoparticle catalyst. Finally, the fuel gas in the solid oxide fuel cell is converted into biomass gas, achieving stable operation when biomass gas is used as fuel.
2. The method for preparing a catalytically active anode flow field plate for use in a solid oxide fuel cell stack according to claim 1, characterized in that, The specific process of structural control of nickel foam in S1 is as follows: The nickel foam is cut into block structures, and then rolled twice on rollers to adjust the thickness and areal density of the nickel foam. The rolled nickel foam is then soaked in dilute hydrochloric acid solution for 5-15 minutes, rinsed with distilled water, and then ultrasonically cleaned in dilute hydrochloric acid solution, anhydrous ethanol, acetone and deionized water for 25-30 minutes respectively. Finally, it is vacuum dried at 50-70℃ for 5-8 hours to obtain a clean nickel foam substrate.
3. A method for preparing a catalytically active anode flow field plate for use in a solid oxide fuel cell stack according to claim 2, characterized in that, The thickness of the nickel foam after the first rolling is 1.2~1.3 mm, the thickness of the nickel foam after the second rolling is 0.9~1.1 mm, and the areal density of the nickel foam after rolling reaches 0.40~0.45 kg / m2; the original thickness of the nickel foam is 1.5 mm; the concentration of the dilute hydrochloric acid solution is 1 mol / L~2 mol / L.
4. The method for preparing a catalytically active anode flow field plate for use in a solid oxide fuel cell stack according to claim 2, characterized in that, The specific process for pre-oxidizing nickel foam in S1 is as follows: The nickel foam substrate is subjected to high-temperature pre-oxidation treatment in air atmosphere at a temperature of 400℃~700℃ and a heating rate of 5~10℃ / min. After reaching the set temperature, it is held for 8~15 minutes. After cooling to room temperature, a nickel foam substrate with nickel oxide on the surface is obtained.
5. The method for preparing a catalytically active anode flow field plate for use in a solid oxide fuel cell stack according to claim 1, characterized in that, The specific process of S2 is as follows: Step 1: Dissolve lanthanum nitrate hexahydrate, nickel nitrate hexahydrate, and tetrabutyl titanate in 80-100 ml of anhydrous ethanol at a mass ratio of 30-40 g: 2-4 g: 25-34 g, then add 40-45 g of citric acid and stir to form solution I; Step 2: Dissolve 20-32 g of ethylenediaminetetraacetic acid in 80-100 ml of deionized water and stir at 80 °C to form solution II; Step 3: Add solution II to solution I, adjust the pH to 7.5-8.5 with ammonia, and stir at 80 °C for 2 hours to obtain the precursor solution of the active component.
6. The method for preparing a catalytically active anode flow field plate for use in a solid oxide fuel cell stack according to claim 1, characterized in that, The specific steps for obtaining the catalyst-supported anode flow field plate after microwave hydrothermal synthesis in S3 are as follows: A nickel foam substrate with nickel oxide on its surface was immersed in a precursor liquid of the active component. It was first heated to 100 °C for 3-5 min, then heated to 180 °C for 2-4 min, and then heated to 200 °C for 1-2 min. It was then held at 200 °C for 60 min and cooled to room temperature to obtain the reacted nickel foam substrate. The surface gel of the reactants on the reacted nickel foam substrate was then removed. The substrate was then washed several times with deionized water and anhydrous ethanol to obtain the catalyst-supported anode flow field plate.
7. The method for preparing a catalytically active anode flow field plate for use in a solid oxide fuel cell stack according to claim 1, characterized in that, The cathode side of the metal connector uses a stainless steel corrugated plate as an air flow field plate, while the anode side of the metal connector uses an anode flow field plate loaded with a catalyst.
8. A catalytically active anode flow field plate for use in a solid oxide fuel cell stack, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.
